A systematic review of the outcomes reported in the treatment of uncomplicated urinary tract infection clinical trials. Issue 2 (22nd March 2022) - Duane, Sinead; Beecher, Claire; Vellinga, Akke; Murphy, Andrew W.; Cormican, Martin; Smyth, Andrew; Healy, Patricia; Moore, Michael; Little, Paul; Devane, Declan
Abstract: Background: Uncomplicated urinary tract infections (UTIs) are amongst the most frequent infections presenting in the outpatient setting. A growing number of clinical trials are assessing the most effective treatment interventions for uncomplicated UTI. Due to the heterogeneity of the outcomes reported in these trials, however, comparing these outcomes is challenging. Objectives: Identify the core outcomes that have been reported in trials and systematic reviews of interventions treating uncomplicated UTI in adults. Methods: We conducted a systematic search for core outcomes used to evaluate treatments of UTIs. We searched the Cochrane Database of Systematic Reviews, PubMed and Embase. One researcher independently screened each article for inclusion, and the Core Outcome Set for treatment of Urinary Tract Infections (COSUTI) team acted as second reviewers. All included articles were screened by two reviewers. All outcomes were extracted verbatim, and similar outcomes were grouped into domains and subdomains. Results: In total, 334 outcomes were reported across 41 papers, the average number of outcomes reported being 8. Outcomes were categorized across 18 domains, the majority of which were related to clinical cure outcomes. Many outcomes varied in the timepoints within which the outcome was measured and reported. Conclusions: Comparing the outcomes of trials investigating uncomplicated UTI treatment remains challenging due to the difference in outcomes currently reported. Consistency of reporting of outcomes would be improved by developing a minimum number of consistent outcomes that should be reported in all trials.